Well-posedness and blow-up of Virial type for some fractional inhomogeneous Choquard equations. Issue 8 (24th May 2022) - Chergui, L.
ABSTRACT: In the subcritical energy case, local well-posedness is established in the radial energy space for a class of fractional inhomogeneous Choquard equations. The best constant of a Gagliardo–Nirenberg type inequality is obtained. Moreover, a sharp threshold of global existence versus blow-up dichotomy is obtained for mass super-critical and energy subcritical solutions.